Targeting Angiogenesis and Tumor Microenvironment in Metastatic Colorectal Cancer: Role of Aflibercept - Guido Giordano; Antonio Febbraro; Michele Venditti; Serena Campidoglio; Nunzio Olivieri; Katia Raieta; Pietro Parcesepe; Giusy Carmen Imbriani; Andrea Remo; Massimo Pancione (Gastroenterology Research and Practice)
In the last decades, we have progressively observed an improvement in therapeutic options for metastatic colorectal cancer (mCRC) treatment with a progressive prolongation of survival. mCRC prognosis still remains poor with low percentage of 5-year survival. Targeted agents have improved results obtained with standard chemotherapy. Angiogenesis plays a crucial role in colorectal cancer growth, proliferation, and metastasization and it has been investigated as a potential target for mCRC treatment. Accordingly, novel antiangiogenic targeted agents bevacizumab, regorafenib, and aflibercept have been approved for mCRC treatment as the result of several phase III randomized trials. The development of a tumor permissive microenvironment via the aberrant expression by tumor cells of paracrine factors alters the tumor-stroma interactions inducing an expansion of proangiogenic signals. Recently, the VELOUR study showed that addition of aflibercept to FOLFIRI regimen as a second-line therapy for mCRC improved significantly OS, PFS, and RR. This molecule represents a valid second-line therapeutic option and its peculiar ability to interfere with placental growth factor (PlGF)/vascular endothelial growth factor receptor 1 (VEGFR1) axis makes it effective in targeting angiogenesis, inflammatory cells and in overcoming resistances to anti-angiogenic first-line treatment. Here, we discuss about Aflibercept peculiar ability to interfere with tumor microenvironment and angiogenic pathway.